THE EFFECT OF ZAKAT, INFAQ, AND SADAQAH ON THE OPEN UNEMPLOYMENT RATE IN INDONESIA - Rizky Fadhillah; Nur Raudhatul RIdha (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to examine the impact of Zakat, Infaq, and Sadaqah on the open unemployment rate in Indonesia. Using a descriptive quantitative method, the study collects secondary data consisting of zakat, infak, and sadaqah distribution from the National Zakat Management Agency's national zakat management report and data on the percentage of open unemployment rates per province in Indonesia from the Regional Profile and Analysis website managed by the National Development Planning Agency over the past five years, specifically the period from 2020 to 2024. This study uses WarpPLS software version 6.0 to analyze the previously collected data. The results of this study indicate that Zakat, Infaq, and Sadaqah have a positive and significant impact on the open unemployment rate. An increase in Zakat, Infaq, and Sadaqah leads to an increase in the open unemployment rate. Based on these findings, all relevant parties—including zakat management bodies, government agencies, and other stakeholders—are encouraged to develop more efficient strategies to reduce unemployment in Indonesia, both through long-term and short-term programs.